2019
DOI: 10.1111/acer.14216
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Pretreatment Trajectories of Alcohol Use and Their Relationship to Treatment Outcome in Men and Women With Alcohol Use Disorder

Abstract: Background: Few studies have focused on behavioral changes that occur prior to entering treatment for an alcohol use disorder (AUD). In 2 studies (Psychol Addict Behav, 27, 2013, 1159 J Stud Alcohol, 66, 2005, 369), pretreatment reductions in alcohol use were associated with better treatment outcomes. Identifying patterns of pretreatment change has the potential to inform clinical decision making.Methods: This study sought to identify pretreatment change trajectories in individuals seeking outpatient treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 55 publications
3
24
2
Order By: Relevance
“…The high rates of PDA at baseline impacted our ability to demonstrate change and may reflect a number of factors. The high rates of PDA at baseline may reflect changes in drinking or substance use before treatment entry commonly found among outpatient treatment samples [66][67][68][69][70][71]. Although we did not see a change in PDA when we compared past 90 days to past 30 days at baseline, we did find a high percentage of the sample had been incarcerated in the baseline time period, which would contribute to higher PDA.…”
Section: Discussioncontrasting
confidence: 56%
“…The high rates of PDA at baseline impacted our ability to demonstrate change and may reflect a number of factors. The high rates of PDA at baseline may reflect changes in drinking or substance use before treatment entry commonly found among outpatient treatment samples [66][67][68][69][70][71]. Although we did not see a change in PDA when we compared past 90 days to past 30 days at baseline, we did find a high percentage of the sample had been incarcerated in the baseline time period, which would contribute to higher PDA.…”
Section: Discussioncontrasting
confidence: 56%
“…Kaminer et al (2008) found that 51.4% of adolescents with alcohol and other substance use disorders reported abstinence from alcohol between intake and first session. Studies with adult populations reveal similar findings (Orford et al, 2006;Kindsvatter et al, 2010;Stasiewicz et al, 2019).…”
Section: Introductionsupporting
confidence: 52%
“…Individuals may have learned through past treatment that seeking treatment provides relief, which prompts them to initiate change. Additionally, pre-treatment change may be associated with lower perceived cost of alcohol use reduction, and individuals having greater confidence, commitment and motivation to abstaining (Stasiewicz et al, 2019). Altogether, these studies demonstrate that a sizeable number of individuals with AUD begin to reduce their drinking prior to treatment.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations